Respiration-Locking of Olfactory Receptor and Projection Neurons in the Mouse Olfactory Bulb and Its Modulation by Brain State - Ackels, Tobias; Jordan, Rebecca; Schaefer, Andreas T.; Fukunaga, Izumi (Frontiers in Cellular Neuroscience, 2020)
For sensory systems of the brain, the dynamics of an animal’s own sampling behaviour has a direct consequence on ensuing computations. This is particularly the case for mammalian olfaction, where a rhythmic flow of air over the nasal epithelium entrains activity in olfactory system neurons in a phenomenon known as sniff-locking. Parameters of sniffing can, however, change drastically with brain states. Coupled to the fact that different observation methods have different kinetics, consensus on the sniff-locking properties of neurons is lacking. To address this, we investigated the sniff-related activity of olfactory sensory neurons (OSNs), as well as the principal neurons of the olfactory bulb (OB), using 2-photon calcium imaging and intracellular whole-cell patch-clamp recordings in vivo, both in anaesthetised and awake mice. Our results indicate that OSNs and OB output neurons lock robustly to the sniff rhythm, but with a slight temporal shift between behavioural states. We also observed a slight delay between methods. Further, the divergent sniff-locking by TCs and MCs in the absence of odour can be used to determine the cell type reliably using a simple linear classifier. Using this classification on datasets where morphological identification is unavailable, we find that MCs use a wider range of temporal shifts to encode odours than previously thought, while TCs have a constrained timing of activation due to an early-onset hyperpolarisation. We conclude that the sniff rhythm serves as a fundamental rhythm but its impact on odour encoding depends on cell type, and this difference is accentuated in awake mice.